Training of School's Mailing Administration Based on Digital in “PAUD Mutiara Kids”, Traji Village, Temanggung District - Hengky Pramusinto; Ismiyati Ismiyati; Nita Dwi Yulianti (Indonesian Journal of Devotion and Empowerment, 2023)
This community service aims to increase the knowledge and skills of Administration employees at Paud Mutiara Kids in managing incoming and outgoing letters to help smooth school activities. The method of implementing activities is planned using a participatory approach, with service work procedures that include training preparation, training implementation, training monitoring and evaluation, mentoring and mentoring monitoring and evaluation. The target of this community service is PAUD KIDS in Traji Village, Temanggung Regency. The results of this service activity, which was carried out on Tuesday, 24 August 2021, at Mutiara Kids Early Childhood Education, Traji Village, Temanggung Regency face-to-face as well as online, material delivery was carried out online via Zoom with a discussion of letter management at work while mentoring was carried out face-to-face with keep following health protocols by using e-agenda software. This activity concludes that the "Training and Assistance for Digital-Based School Letter Administration Management at Early Childhood Education in Traji Village, Temanggung Regency" community service activity has been carried out well, received good feedback, and participants expect the training event to be held again. This activity suggests that community service activities are expected to be carried out regularly and targets that really need them. Pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pengetahuan dan ketrampilan pegawai Tata Usaha di Paud Mutiara Kids dalam mengelola surat masuk dan surat keluar sehingga membantu kelancaran kegiatan sekolah. Metode pelaksanaan kegiatan direncanakan dengan menggunakan pendekatan partisipatif, dengan prosedur kerja pengabdian yang meliputi persiapan pelatihan, pelaksanaan pelatihan, pemantauan dan evaluasi pelatihan, pendampingan dan pemantauan dan evaluasi pendampingan. Sasaran dari pengabdian kepada masyarakat ini yaitu PAUD KIDS Desa Traji Kabupaten Temanggung. Hasil kegiatan dari pengabdian ini yang dilaksanakan pada hari Selasa, 24 Agustus 2021 di Paud Mutiara Kids, Desa Traji Kabupaten Temanggung secara tatap muka dan juga daring, pemberian materi dilaksanakan secara daring melalui zoom dengan pembahasan pengelolaan surat ditempat kerja sedangkan pendampingan dilakukan secara tatap muka dengan tetap mengikuti protokol kesehatan dengan menggunakan software e-agenda. Simpulan dari kegiatan ini adalah kegiatan pengabdian kepada masyarakat “Pelatihan dan Pendampingan Tata Kelola Administrasi Persuratan Sekolah Berbasis Digital di Paud Kids Desa Traji, Kabupaten Temanggung” telah terlaksana dengan baik, mendapatkan feedback yang baik dan peserta mengharapkan acara pelatihan diselenggrakan kembali. Saran dalam kegiatan ini adalah diharapkan kegiatan pengabdian dilakukan secara rutin serta sasaran yang benar-benar membutuhkan.